Evolution of the Relative Price of Goods and Services in a Neoclassical Model of Capital Accumulation - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2004)
This paper provides an explanation for the secular increase in the price of services relative to that of manufactured goods that relies on capital accumulation rather than on an exogenous total factor productivity growth differential. The key assumptions of the two-sector, intertemporal optimizing model are relatively high capital intensity in the production of goods and limited cross-border capital mobility, allowing the interest rate to vary. With plausible parameterization, the model also predicts a decline in the employment share of the goods sector over time.